If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p = 12x + -5x Combine like terms: 12x + -5x = 7x p = 7x Solving p = 7x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Simplifying p = 7x
| 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 |